Revolusi Mental Berbasis Al-Qur’an Penangkal Pergaulan Bebas Remaja - sumiyati sumiyati (Syntax Idea, 2022)
Nowadays, many teenagers' promiscuity is getting affected, where many cases after cases are related to juvenile delinquency. There are many factors that cause promiscuity among adolescents, the most dominant of which is caused by the formation of the wrong educational character in the family environment. The research methods used in solving problems include analytical methods. Image captions are placed as part of the image title (figure caption) and not as part of the image. Modern life is where everything has changed drastically in terms of technology, science and so on. Practical life is pampered with various kinds of technological facilities that make it easier for humans to interact with each other. The ease of technology obtained by humans makes the culture of society gradually eroded by the times. Teenagers face various kinds of problems which are often difficult to solve. The problems that exist among adolescents are extreme and the impact is enormous. One example that becomes a joint homework that must be completed immediately is the way of promiscuity of teenagers.